Topography and Permanently Shaded Regions (PSRs) 87°S to Pole of the Moon - Stopar, Julie; orcid:0000-0003-1578-3688; Meyer, Heather M.; orcid:0000-0002-6888-9868 (Lunar and Planetary Institute, Regional Planetary Image Facility, 2019)
This map is based on data released by the Lunar Reconnaissance Orbiter Lunar Orbiter Laser Altimeter (LOLA). The map is centered on the south pole and shows the LOLA 5-m elevation product between 85°S and the pole (NASA Goddard Space Flight Center; Smith et al., 2010; Smith et al., 2017). The elevation data are overlain on a derived hillshade with solar azimuth 45°W and solar elevation 45°. Permanently shaded regions (PSRs) larger than 10 km2 digitized by Arizona State University and determined by Mazarico et al. (2011) are shown as gray outlines. 1000-m elevation contours (relative to global radius) are shown as green lines with elevations marked. Polar stereographic projection is used with scale true at the pole. Selected feature names are included on the map. [Note: This map was not controlled using the techniques of Glaser et al. (2014, 2018), thus there are artifacts in LOLA track offsets.]